KARAKTERISTIK KONSUMEN BERWAWASAN LINGKUNGAN DAN HUBUNGANNYA DENGAN KEPUTUSAN MEMBELI PRODUK RAMAH LINGKUNGAN - Setyo Ferry Wibowo (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
ABSTRACT The shifting of business trend which is more environmental friendly over the time need to be responded by strategic and systematic marketing efforts to achieve its transactional goals; creating or encouraging purchase. These efforts are important since environmentally friendly products ( green products) tend to have negative trade off, which is low perceived value of the product due to higher cost (e.g.prices) and low benefits (e.g. the loss of some attributes). In this regard, identifying characteristics of green consumers become important since it will serve accurate profile of green consumers, which is very useful in formulating marketing strategies and tactics. The purpose of this study is to determine relationship between green consumers' psychographic characteristics, namely: environmental concern, brand orientation and the opinions of reference for social groups (opinion leadership), with a decision to buy green products. The research population was mall visitors who consume green products. Factor analysis and multiple regression are used to analyze data. Results of the analysis are: green consumers' psychographic characteristics, namely: environmental concern, brand orientation and the opinions of reference for social groups (opinion leadership) have association with a decision to buy green products.Keywords: green marketing, green products, green consumers, green advertising